BOBOT BADAN AKHIR DAN PERSENTASE BONELESS BROILER YANG DIBERIKAN BUNGKIL INTI SAWIT SEBAGAI PAKAN SUBTITUSI DEDAK PADI - Muhammad Nur Hidayat (Wahana Peternakan, 2022)
This study aims to examine the response of final body weight and growth of broiler chest muscle given fermented and unfermented palm kernel cake as raw material for substitution of rice bran in broiler rations. This study used a completely randomized design consisting of 5 treatments and 4 replications filled with 2 chickens each. The treatments consisted of P0 (control), P1 (10% palm kernel cake), P2 (10% fermented palm kernel cake), P3 (15% fermented palm kernel cake), and P4 (20% palm kernel cake). The results showed that the treatment had a significant effect (P<0.05) on the final weight or slaughter weight and the percentage of boneless breast meat, but had no significant effect (P>0.05) on the percentage of breast bone and the ratio of bone meat. The addition of palm kernel cake up to 15% can increase the boneless broiler breast meat, although it tends to reduce the final weight of the broiler. So that the substitution of rice bran with fermented palm kernel cake can be replaced by up to 15%. Keywords: Palm kernel cake, Boneless, Boneless broiler meat, Meat and bone ratio